Landsat 8 oli Satellite Imagery Mapping and Analysis of Bedrock Fracture Networks in the Departments of Yamoussoukro and Toumodi (Central Cote d’Ivoire) - Guillaume, Atte; Arthur Brice, Konan-Waidhet; Parfait, Sombe Abé; Hervé Jacques, Kokobou Kouassi; Jea, Biemi (European Scientific Journal, ESJ, 2022)
This study focuses on the departments of Yamoussoukro and Toumodi located in central Côte d’Ivoire where the problem of drinking water supply is a growing reality. Its objective is to map and analyze the fracturing likely to develop underground aquifers from Landsat 8 OLI data. The set of techniques (color composition, directional and gradient filters) used resulted in the enhancement of linear structures present on satellite images, allowing a better mapping of geological features. The linear map obtained, after the different treatments, is very dense and includes 2063 lineaments. The validation of these different linear structures was made on the basis of the drillings already carried out from the data of the geophysics. The analysis of the fracture networks emphasized two dominant directions, namely: N0°-10° (N-S) and N90°-100° (E-W), which highlights the heterogeneity of the geological formations. These results constitute an essential contribution to the exploitation of groundwater resources in the departments of Yamoussoukro and Toumodi.